2021
DOI: 10.1186/s12942-021-00287-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors affecting individual GPS-based activity space and how researcher-defined food environments represent activity space, exposure and use of food outlets

Abstract: Background Obesity remains one of the most challenging public health issues of our modern time. Despite the face validity of claims for influence, studies on the causes of obesity have reported the influence of the food environment to be inconsistent. This inconsistency has been attributed to the variability of measures used by researchers to represent the food environments—Researcher-Defined Food Environments (RDFE) like circular, street-network buffers, and others. This study (i.) determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…This includes, for example, generating activity spaces based on all GPS points, so both locations and routes between locations, while other studies only base food retailer exposures on GPS-derived locations. Such processing decisions likely significantly affect the results [ 27 ] because generating activity spaces based on all GPS points captures all potential food outlets within that activity space. Using retailer-based exposures only can result in potential underestimations of exposure [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes, for example, generating activity spaces based on all GPS points, so both locations and routes between locations, while other studies only base food retailer exposures on GPS-derived locations. Such processing decisions likely significantly affect the results [ 27 ] because generating activity spaces based on all GPS points captures all potential food outlets within that activity space. Using retailer-based exposures only can result in potential underestimations of exposure [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such processing decisions likely significantly affect the results [ 27 ] because generating activity spaces based on all GPS points captures all potential food outlets within that activity space. Using retailer-based exposures only can result in potential underestimations of exposure [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“… 63 This complex relationship between exposure to food outlets and its use has been highlighted by others as well. 64 To address this gap, future research could explore the link between actual use of food outlets (by measuring daily activity patterns of participants) and reported use of food outlets, and its relation with overweight.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison by Burgoine and Harrison (2013) of food PoI data with local authority held data showed that PoI data were a viable substitute, and that this conclusion was robust to cover urban/rural and socioeconomic divides. PoI data have also been used in other studies from the domains of crime (Hunter, 2020;Redfern et al, 2020), area classifications (Niu & Silva, 2021), health (Hobbs et al, 2019) and defining activity spaces (Marwa et al, 2021).…”
Section: Methodsmentioning
confidence: 99%